High thermoelectric performance bismuth telluride prepared by cold pressing and annealing facilitating large scale application. (November 2021) - Wang, W.; Sun, Y.; Feng, Y.; Qin, H.; Zhu, J.; Guo, F.; Cai, W.; Sui, J.
Abstract: Bi2 Te3 -based alloys, generally prepared by traditional zone melting or hot-pressing, have been used in commercial applications for decades. However, the zone melting method is time-consuming and usually accompanied by poor thermoelectric performance, while the hot-pressing sintering needs complex and high-cost equipment. In this work, high-performance p-type Bi0.4 Sb1.6 Te3 alloy is prepared by cold pressing the ball milled Bi0.4 Sb1.6 Te3 powder followed by vacuum annealing, which is more suitable for large-scale promoting with cost saving. Owing to the low lattice thermal conductivity brought by fine grains, a peak ZT value of ∼1.15 at 50 °C and an average ZT value of ∼0.84 within 30–250 °C are realized, which are comparable with the excellent performance achieved by zone melting and hot-pressing, and are even better than that of the optimized cold-pressed sample. More importantly, the thermoelectric performance here shows good repeatability from batch to batch. Our work makes the widespread application of Bi0.4 Sb1.6 Te3 alloy in thermoelectric power generation and refrigeration an important step forward. Graphical abstract: Image 1 Highlights: Bi0.4 Sb1.6 Te3 is prepared by cold pressing the nano powder and annealing. The sufficient connection among nanocrystals causes good electrical properties. The ultra-fine grains bring about low thermal conductivity. A high ZT value of ∼1.15 at 50 °C is achieved for Bi0.4 Sb1.6 Te3 .